Lost Trust? The Experiences of Teachers and Students during Schooling Disrupted by the Covid-19 Pandemic - Tijana Jokić Zorkić; Katarina Mićić; Tunde Kovacs Cerović (Center for Educational Policy Studies Journal)
This paper aims to help understand how relational trust between students and teachers embedded in the teaching-learning process unfolded during the emergency distance and flexible hybrid education in Serbia in 2020. It also identifies niches in student-teacher relationships that hold potential for repairing and building trust. For the student-teacher relationship to be trust-based and thus conducive to students’ learning and wellbeing, a consensus about role expectations must be achieved. As the Covid-19 crisis interrupted schooling and education, participants faced uncertainties and ambiguities in role enactment, and the cornerstones of relational trust were disrupted. In an effort to understand 1) the context in which trust was challenged, 2) the ways in which trust was disrupted, and 3) the opportunities for its restoration, we relied on a multi-genre dynamic storytelling approach to data collection and values analysis for data processing. A total of 136 students and 117 teachers from 22 schools wrote 581 narratives in three genres: stories, letters and requests. The analysis yielded 22 codes that allowed further understanding of how changes in structural and institutional conditions affected both students’ and teachers’ expectations of each other, and how incongruence of these expectations fed into feelings of helplessness for both students and teachers, disengagement from learning for students, and heavy workload and poor performance for teachers. In addition, the narratives account for positive outcomes when these expectations were met, and for opportunities for trust-building if students’ and teachers’ perspectives are brought to each other’s attention and negotiated locally. Finally, recommendations for restoring trust are given.